2017
DOI: 10.17135/jdhs.2017.17.3.250
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among Maternal Sociodemographics, Oral Health Behavior, and the Prevalence of Early Childhood Caries

Abstract: The purpose of this study was to examine the influence of maternal socioeconomic status, maternal oral health behaviors, and oral health behaviors of children, on the prevalence of early childhood caries in children aged 5 years. The Korean National Health and Nutrition Examination Survey data collected between 2007 and 2014 were applied to this study, and the study sample included 824 children who received oral examinations and participated in the health behavior survey. The factor that affected the prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…In agreement with other studies, we found that children whose mothers were homemakers, students, or pensioners (i.e., having no permanent income) were 87% more likely than their counterparts to be in the severe caries category (Kang et al 2017; van der Tas et al 2017). Findings from a study in India revealed that mother’s occupation was significantly associated with the caries status of her children, wherein children whose parents were in white-collar occupations experienced lesser caries (Tadakamadla et al 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with other studies, we found that children whose mothers were homemakers, students, or pensioners (i.e., having no permanent income) were 87% more likely than their counterparts to be in the severe caries category (Kang et al 2017; van der Tas et al 2017). Findings from a study in India revealed that mother’s occupation was significantly associated with the caries status of her children, wherein children whose parents were in white-collar occupations experienced lesser caries (Tadakamadla et al 2012).…”
Section: Discussionsupporting
confidence: 93%